RSIS-WTO Parliamentarian Workshop – US-China Trade War : Emerging Dilemmas - Lee, Su-Hyun (2019)
The US-China trade war has been rapidly escalating into an economic and political warfare between the two big powers. The fundamental transformation of US-China relations will reshape the global order and create economic and diplomatic dilemmas for many other countries.